Exposing the film apparatus the film archive as a research laboratory - Fossati, Giovanna 1971-; Oever, Annie van den 1957- (Amsterdam University Press, 2016)
Film archives have long been dedicated to preserving movies, and they've been nimble in recent years in adapting to the changing formats and technologies through which cinema is now created and presented. This collection makes the case for a further step: the need to see media technologies themselves as objects of conservation, restoration, presentation, and research, in both film archives and film studies. Contributors with a wide range of expertise in the film and media world consider the practical and theoretical challenges posed by such conservation efforts and consider their potential to generate productive new possibilities in research and education in the field
Keywords: Medientechnik; Filmarchiv; Filmmuseum; Konferenzschrift -- 2013 -- Groningen